2013
DOI: 10.1021/am402585y
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Fe3O4Polydopamine Nanoparticles Serve Multipurpose as Drug Carrier, Catalyst Support and Carbon Adsorbent

Abstract: We present the synthesis and multifunctional utilization of core-shell Fe3O4 polydopamine nanoparticles (Fe3O4@PDA NPs) to serve as the enabling platform for a range of applications including responsive drug delivery, recyclable catalyst support, and adsorbent. Magnetite Fe3O4 NPs formed in a one-pot process by the hydrothermal approach were coated with a polydopamine shell layer of ~20 nm in thickness. The as prepared Fe3O4@PDA NPs were used for the controlled drug release in a pH-sensitive manner via reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
218
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 350 publications
(223 citation statements)
references
References 31 publications
2
218
0
3
Order By: Relevance
“…The advantages can be exhibited from the following aspects: i) dopamine, the PDA monomer that contains both catechol and amine functional groups, self-polymerizes at alkaline pH values (Lee et al 2007;Liu et al 2013). During polymerization, PDA will form a conformal and continuous coating layer at nearly any material surface including noble metals, metal oxides, semiconductors, ceramics, and synthetic polymers via the strong binding affinity of catechol functional groups (Lee et al 2007); ii) the thickness of PDA layer may be readily controlled by varying the dopamine concentration and reaction time (Liu et al 2013); iii) PDA can serve as an adhesion layer to immobilize biological molecules, amine-and mercapto functionalized self-assembled monolayers, and metal films (Bernsmann et al 2008;He et al 2005;Liu et al 2006;Ryu et al 2010); iv) PDA can reduce metal salts into metal nanoparticles via the catechol functional groups (Guo et al 2012). A range of metals including Au, Ag, Pt and Cu have been successfully reduced and deposited on PDA modified surfaces without the addition of a reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages can be exhibited from the following aspects: i) dopamine, the PDA monomer that contains both catechol and amine functional groups, self-polymerizes at alkaline pH values (Lee et al 2007;Liu et al 2013). During polymerization, PDA will form a conformal and continuous coating layer at nearly any material surface including noble metals, metal oxides, semiconductors, ceramics, and synthetic polymers via the strong binding affinity of catechol functional groups (Lee et al 2007); ii) the thickness of PDA layer may be readily controlled by varying the dopamine concentration and reaction time (Liu et al 2013); iii) PDA can serve as an adhesion layer to immobilize biological molecules, amine-and mercapto functionalized self-assembled monolayers, and metal films (Bernsmann et al 2008;He et al 2005;Liu et al 2006;Ryu et al 2010); iv) PDA can reduce metal salts into metal nanoparticles via the catechol functional groups (Guo et al 2012). A range of metals including Au, Ag, Pt and Cu have been successfully reduced and deposited on PDA modified surfaces without the addition of a reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it was reported that during the solvothermal preparation procedure of Fe 3 O 4 , EG also acted as the reductant of Fe 3+ . [38,39] As such, EG plays the role of reductant and solvent in the systematic preparation of Fe 3 O 4 /Cu. Figure 4.…”
Section: +mentioning
confidence: 99%
“…[32] During the polymerization, DA spontaneously forms a uniform, continuous, and cross-linked homopolymer (polydopamine (PDA)) on adhesive materials with abundant amine groups and phenolic hydroxyl groups, which are beneficial for anchoring and growing metal nanoparticles. [33][34][35][36] By taking advantage of its versatile coating capacity through noncovalent adsorption, PDA can be considered as a promising modifier for the functionalization of graphene oxide and serves as a molecular linker to anchor and disperse Pt nanoparticles on the surface of graphene.…”
Section: Introductionmentioning
confidence: 99%